Severity of Anosmia as an Early Symptom of COVID-19 Infection May Predict Lasting Loss of Smell - Lechien, Jerome R.; Journe, Fabrice; Hans, Stephane; Chiesa-Estomba, Carlos M.; Mustin, Vincent; Beckers, Eline; Vaira, Luigi A.; De Riu, Giacomo; Hopkins, Claire; Saussez, Sven (Frontiers in Medicine, 2020)
Abstract Introduction: To evaluate the recovery rate of loss of smell (LOS) with objective olfactory testing in COVID-19 patients. Methods: Adults with confirmed COVID-19 and self-reported sudden LOS were prospectively recruited through a public call from the University of Mons (Belgium). Epidemiological and clinical data were collected using online patient-reported outcome questionnaires. Patients benefited from objective olfactory evaluation (Sniffin-Sticks test) and were invited to attend for repeated evaluation until scores returned to normal levels. Results: From March 22 to May 22, 2020, 88 patients with sudden onset LOS completed the evaluations. LOS developed after general symptoms in 44.6% of cases. Regarding objective evaluation, 22 patients (25.0%) recovered olfaction within 14 days following the onset of LOS. The smell function recovered between the 16th and the 70th day post-LOS in 48 patients (54.5%). At the time of final assessment at 2 months, 20.5% of patients (N=18) had not achieved normal levels of olfactory function. Higher baseline severity of olfactory loss measured using Sniffin-Sticks was strongly predictive of persistent loss (p<0.001). Conclusion: In the first 2 months, 79.5% of patients may expect to have complete recovery of their olfactory function. The severity of olfactory loss, as detected at the first Sniffin-Sticks test, may predict the lack of mid-term recovery.